Évolution des ponts et du lit mineur de la Loire, entre La Charité-sur-Loire et la Chapelle-Montlinard - Annie Dumont; Marion Foucher; Ronan Steinmann; Catherine Lavier; Philippe Moyat; Jean-Pierre Garcia (Développement Durable et Territoires)
The Loire River is the longest river in France, where the building of bridges and their long-term maintenance have never been easy tasks, because of strong currents and frequent floods. At a distance of 500 km from its source, between La Charité-sur-Loire and La Chapelle-Montlinard, the remains of a medieval bridge were recently discovered. A multidisciplinary approach is used to reconstruct the long history of building maintenance and re-building of these bridges, which occurred several times, over eight centuries, after their destruction by natural causes or human activity. For this purpose, the study of archival literature (texts and maps) was combined with underwater archaeology, dendrochronology, building archaeology, and geomorphological landscape analyses. Although this is an ongoing research project, sufficient data have been collected to allow the presentation of a preliminary series of results.